Epigenetic conflict on a degenerating Y chromosome increases mutational burden in Drosophila males - Kevin H.-C. Wei (Nature Portfolio, 2020)
Selfish DNA such as transposable elements cause intragenomic conflict. This study finds that on an evolutionarily young, gene-rich Drosophila Y chromosome, transposable elements evade heterochromatic suppression, leading to elevated transposition rates in males.